2018
DOI: 10.1111/hsc.12634
|View full text |Cite
|
Sign up to set email alerts
|

Are reasons for care‐giving related to carers’ care‐related quality of life and strain? Evidence from a survey of carers in England

Abstract: In England, choice and control is promoted for service users in relation to social care services. Increased choice and control has also been promoted for unpaid carers, although this is still relatively underdeveloped. There is limited recognition of carers' choice in terms of the decision of whether to provide care. Alongside the promotion of choice and control, there has also been a focus on quality of life as an outcome of social care for care-recipients and their carers. Although it is known that carer cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…The finding that lack of choice, both in terms of taking up the caregiving role and the perceived degree of choice in caregiving, was not associated with poorer caregiver health, and well-being outcomes was unexpected. It is, however, in line with one study which found that willingness to care did not significantly predict quality of life or strain (Rand et al, 2019). It is possible that our findings differed from other studies because we assessed relationships over time, rather than cross-sectionally; however, few significant correlations were observed between our measures of choice and caregiver outcomes even at baseline.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The finding that lack of choice, both in terms of taking up the caregiving role and the perceived degree of choice in caregiving, was not associated with poorer caregiver health, and well-being outcomes was unexpected. It is, however, in line with one study which found that willingness to care did not significantly predict quality of life or strain (Rand et al, 2019). It is possible that our findings differed from other studies because we assessed relationships over time, rather than cross-sectionally; however, few significant correlations were observed between our measures of choice and caregiver outcomes even at baseline.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, studies that have examined reasons for caregiving, which are tied to caregiver choice, have also found associations with poorer caregiver wellbeing. For example, the perceived lack of availability or suitability of other care options predicted poorer care-related quality of life in a mixed sample of English caregivers, though no significant relationships were observed between personal choice/willingness to care, and measures of quality of life or strain (Rand et al, 2019). Other studies suggest that intrinsic motivations to care are associated with positive caregiver mental health, while external motivations or pressures predict negative outcomes such as stress, anxiety, depression, and anger (Lyonette and Yardley, 2003; Losada et al, 2010; Romero-Moreno et al, 2011; Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Being a carer is associated with poorer mental and physical health (Hiel et al, ; Peters, Jenkinson, Doll, Playford, & Fitzpatrick, ; Thomas, Saunders, Roland, & Paddison, ) and poorer experiences of using primary care (Thomas et al, ). A study of carers in England found that people who choose to be carers had better quality of life and less carer strain than people who provided care as it was expected of them (Rand, Malley, & Forder, ). Poorer experiences of services are associated with poorer carer quality of life (Peters et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of sABI are known to affect not only the patients themselves but also their families. Indeed, regardless of the severity of the injury, family members often feel high levels of strain both in the in‐hospital admission and in the discharge phases because individuals with sABI are for the most part unable to manage their social life and dramatically depend on them (Bivona et al., 2015; D’Ippolito et al., 2018; Koskinen, 1998; Kratz, Sander, Brickell, Lange, & Carlozzi, 2017; Kreutzer et al., 2018; Rand, Malley, & Forder, 2019). The higher risk of strain is, anyhow, for the family member (a relative or a close friend) who acts as an informal caregiver (hereafter, IC) and specifically cares for the loved one with significant health issues, through voluntary and unpaid help, regardless of their experience or specialised knowledge (Spann et al., 2019).…”
Section: Introductionmentioning
confidence: 99%